2015
DOI: 10.1016/j.celrep.2015.11.009
|View full text |Cite
|
Sign up to set email alerts
|

LUBAC-Recruited CYLD and A20 Regulate Gene Activation and Cell Death by Exerting Opposing Effects on Linear Ubiquitin in Signaling Complexes

Abstract: SummaryUbiquitination and deubiquitination are crucial for assembly and disassembly of signaling complexes. LUBAC-generated linear (M1) ubiquitin is important for signaling via various immune receptors. We show here that the deubiquitinases CYLD and A20, but not OTULIN, are recruited to the TNFR1- and NOD2-associated signaling complexes (TNF-RSC and NOD2-SC), at which they cooperate to limit gene activation. Whereas CYLD recruitment depends on its interaction with LUBAC, but not on LUBAC’s M1-chain-forming cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
414
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 257 publications
(434 citation statements)
references
References 61 publications
19
414
0
1
Order By: Relevance
“…77 Whereas CYLD directly binds LUBAC and removes linear chains, thereby sensitizing cells to TNF-provoked apoptosis, A20 binding to the linear chains via its ZnF7 domain antagonizes their removal, consequently blocking cell death. 78 Dissimilarly, the RIP1-independent apoptotic branch is controlled by the level of cellular FLICE Inhibitory Protein (c-FLIPL), which effectively blocks caspase-8 activation by competitively binding to FADD. The E3 ligase Itch activated by JNK1 phosphorylation acts to provoke apoptosis by directing c-FLIPL for proteasomal destruction.…”
Section: Apoptosis Regulation By the Ubiquitin Systemmentioning
confidence: 99%
“…77 Whereas CYLD directly binds LUBAC and removes linear chains, thereby sensitizing cells to TNF-provoked apoptosis, A20 binding to the linear chains via its ZnF7 domain antagonizes their removal, consequently blocking cell death. 78 Dissimilarly, the RIP1-independent apoptotic branch is controlled by the level of cellular FLICE Inhibitory Protein (c-FLIPL), which effectively blocks caspase-8 activation by competitively binding to FADD. The E3 ligase Itch activated by JNK1 phosphorylation acts to provoke apoptosis by directing c-FLIPL for proteasomal destruction.…”
Section: Apoptosis Regulation By the Ubiquitin Systemmentioning
confidence: 99%
“…Met1-Ub chains are assembled by the linear ubiquitin chain assembly complex (LU-BAC), composed of HOIP, HOIL-1, and SHARPIN [1]. LUBAC function is regulated by the deubiquitinases (DUBs) OTULIN [2-4] and CYLD [5][6][7], which both associate with the catalytic subunit HOIP [5][6][7][8].Previous studies have revealed that OTULIN exclusively hydrolyzes Met1-Ub, prevents accumulation of Met1-Ub on LUBAC components under basal conditions, and restricts ubiquitination of LUBAC substrates after receptor stimulation [2][3][4]. However, the contribution of OTULIN to regulation of physiological immune responses had not been investigated.…”
mentioning
confidence: 99%
“…Met1-Ub chains are assembled by the linear ubiquitin chain assembly complex (LU-BAC), composed of HOIP, HOIL-1, and SHARPIN [1]. LUBAC function is regulated by the deubiquitinases (DUBs) OTULIN [2-4] and CYLD [5][6][7], which both associate with the catalytic subunit HOIP [5][6][7][8].…”
mentioning
confidence: 99%
See 2 more Smart Citations